Gender, Entrepreneurial Self–Efficacy, and Entrepreneurial Career Intentions: Implications for Entrepreneurship Education - Wilson, Fiona; Kickul, Jill; Marlino, Deborah (Entrepreneurship Theory and Practice, 2007)
The relationships between gender, entrepreneurial self–efficacy, and entrepreneurial intentions were examined for two sample groups: adolescents and adult master of business administration (MBA) students. Similar gender effects on entrepreneurial self–efficacy are shown for both groups and support earlier research on the relationship between self–efficacy and career intentions. Additionally, the effects of entrepreneurship education in MBA programs on entrepreneurial self–efficacy proved stronger for women than for men. Implications for educators and policy makers were discussed, and areas for future research outlined.